2021
DOI: 10.1038/s41598-020-80306-0
|View full text |Cite
|
Sign up to set email alerts
|

The alga Euglena gracilis stimulates Faecalibacterium in the gut and contributes to increased defecation

Abstract: The alga Euglena gracilis (E. gracilis) has recently gained attention as a health food, but its effects on human gut microbiota remain unknown. This study aimed to determine the effect of E. gracilis on gut microbiota and defecation due to modulation of microbiota composition in vitro and in vivo. The in vitro model simulating human colonic microbiota revealed that E. gracilis addition stimulated the growth of commensal Faecalibacterium. Further, E. gracilis addition enhanced butyrate production by Faecalibact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 39 publications
2
26
1
Order By: Relevance
“…33 In an in vitro model culture system simulating the microbiota of the human colon, the addition of Euglena enhanced butyrate production by stimulating the growth of Faecalibacterium. 22 In mice, SCFA levels in the feces and serum exhibited a nominal increase after feeding of the Euglena diet, although the effect did not reach statistical significance. 34 Euglena may alleviate constipation in ISO-treated mice in part by restoring the production of SCFAs in the gut.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…33 In an in vitro model culture system simulating the microbiota of the human colon, the addition of Euglena enhanced butyrate production by stimulating the growth of Faecalibacterium. 22 In mice, SCFA levels in the feces and serum exhibited a nominal increase after feeding of the Euglena diet, although the effect did not reach statistical significance. 34 Euglena may alleviate constipation in ISO-treated mice in part by restoring the production of SCFAs in the gut.…”
Section: Discussionmentioning
confidence: 94%
“…21 It is also possible that oral administration of Euglena may maintain healthy gut microbiota and ameliorate intestinal function, because some components of Euglena stimulate the growth of butyrate-producing bacteria in the gut. 22 In this study we examined the effects of Euglena on constipation and cardiac dysfunction in a mouse model of isoproterenol (ISO)-induced HF.…”
Section: Real-time Quantitative Reverse Transcription-polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…Paramylon (PM) is a β-1,3-glucan, found in Euglena gracilis at levels of 20-70% (dry weight basis). It has been reported that PM has various effects, including an immunomodulating effect [13][14][15]. β-1,3-glucan has a triple helix structure and is classified as an insoluble dietary fiber [16]; therefore, it is considered that the physiological properties of PM differ from those of cereal β-glucan or yeast and fungal β-glucan.…”
Section: Introductionmentioning
confidence: 99%
“…gracilis is a unicellular green microalga with flagellar motility (Buetow, 1968). The presence of nutritionally crucial chemicals such as fatty acids, docosahexaenoic acid, eicosapentaenoic acid, and vitamins in E. gracilis implies that this alga is a valuable therapeutic resource with potential for clinical application (Kottuparambil et al, 2019;Nakashima et al, 2021). The paramylon yield from E. gracilis is approximately 60%-70% of the dried cells, and paramylon exhibits antiinflammatory, antimicrobial, antioxidant, anticancer, and neuroprotective properties, as well as immune activating effects (Sakagami et al, 1991;Foltínová et al, 1994;Sugiyama et al, 2009;Russo et al, 2016;Nakashima et al, 2017;Suzuki et al, 2018;Guo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The author reported a decrease in deformability and an increase in cutaneous vitality of skin after 14 days treatment with 3% Euglena extract. Nevertheless, E. gracilis components, other than paramylon, stimulate the growth of Faecalibacterium and improve digestive health (Nakashima et al, 2021). Hence, we investigated whether live E. gracilis cells and its aqueous extract exert beneficial effects on skin wound healing.…”
Section: Introductionmentioning
confidence: 99%